INCIDENCE OF RETINAL REDETACHMENT AFTER ROSO IN PATIENTS OF RRD TREATED VIA PPV WITH AND WITHOUT 360- DEGREE LASER RETINOPEXY (The Research of Medical Science Review, 2024)
Objective: To evaluate the incidence of retinal redetachment after removal of silicone oil (ROSO) in patients with rhegmatogenous retinal detachment (RRD) treated via pars plana vitrectomy (PPV), comparing outcomes between those treated with 360-degree laser retinopexy and focal laser retinopexy. Methods: This retrospective study included 65 patients with primary RRD treated with PPV and silicone oil tamponade. Patients were divided into two groups: Group A (33 patients), who received 360-degree laser retinopexy, and Group B (32 patients), who underwent focal laser retinopexy. The incidence of retinal redetachment after ROSO, visual acuity outcomes, and associated risk factors were analyzed. Statistical tests included chi-square and logistic regression analyses. Results:The incidence of retinal redetachment was significantly lower in Group A (6.1%) compared to Group B (28.1%) (p = 0.03). Visual acuity improved in both groups, with Group A achieving better postoperative BCVA (0.8 ± 0.2 logMAR) than Group B (1.1 ± 0.3 logMAR) (p = 0.04). Risk factors for redetachment included the absence of 360-degree laser retinopexy, PVR Grade C or higher, and prolonged silicone oil tamponade (>4 months). Conclusion: 360-degree laser retinopexy significantly reduces the risk of retinal redetachment after ROSO and improves visual outcomes compared to focal laser retinopexy. This technique is effective and safe, particularly in high-risk cases, and should be considered in surgical planning for RRD management.